Reconstruction of SakÄ«nah Family Criteria During the Covid-19 Period - Yaqub, Andi; Iswandi, Iswandi; Nur, Jabal (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2021)
This article describes the implementation and achievements of the sakÄ«nah family during the Covid-19 period. Both refer to the technical guidelines of the Indonesian Ministry of Religious Affairs in 2011 regarding the criteria for the sakÄ«nah family. This study uses sociological and al-maá¹£laá¸¥ah approaches. The research location is in Konda District, Konawe Selatan Regency. The researchers obtained data from the Office of Religious Affairs (KUA), sub-district government, village heads, community leaders, and the public. This study found that the criteria for the sakÄ«nah family were irrelevant to apply. The reason is that the expectations of these criteria are too high, especially in the fields of economy and social status. In addition, the KUA officers did not implement the sakÄ«nah family counselling properly. Thus, the criteria for the sakÄ«nah family need to be simplified and adapted to the conditions and characteristics of each region.